Intrathecal administration of mesenchymal stem cells in patients with adrenomyeloneuropathy - Siwek, Tomasz; Zwiernik, Beata; Jezierska-Woźniak, Katarzyna; Jezierska, Kamila; Mycko, Marcin P.; Selmaj, Krzysztof W. (Frontiers in Neurology, 2024)
Background and objectives X-linked adrenomyeloneuropathy (AMN) is an inherited neurodegenerative disorder associated with mutations in the ABCD1 gene and the accumulation of very long-chain fatty acids (VLFCAs) in plasma and tissues. Currently, there is no effective treatment for AMN. We have aimed to evaluate the therapeutic effects of mesenchymal stem cell (MSC) transplantation in patients with AMN. Methods This is a small cohort open-label study with patients with AMN diagnosed and treated at the University Hospital in Olsztyn, Poland. All patients met clinical, biochemical, MRI, and neuropsychological criteria for AMN. MSCs derived from Wharton jelly, 20 × 106 cells, were administered intrathecally three times every 2 months, and patients were followed up for an additional 3 months. The primary outcome measures included a blinded assessment of lower limb muscle strength with the Medical Research Council Manual Muscle Testing scale at baseline and on every month visits until the end of the study. Additional outcomes included measurements of the timed 25-feet walk (T25FW) and VLFCA serum ratio. Results Three male patients with AMN with an age range of 26–37 years participated in this study. All patients experienced increased muscle strength in the lower limbs at the end of the study versus baseline. The power grade increased by 25–43% at the baseline. In addition, all patients showed an improvement trend in walking speed measured with the T25FW test. Treatment with MSCs in patients with AMN appeared to be safe and well tolerated. Discussion The results of this study demonstrated that intrathecal administration of WJ-MSC improves motor symptoms in patients with AMN. The current findings lend support to the safety and feasibility of MSC therapy as a potentially viable treatment option for patients with AMN.